Immunological disease induced by injecting F1 lymphoid cells into certain parental strains - Simpson, Elizabeth (1974)
Injection of neonatal Balb/c or C57Bl/6 mice with C57Bl/6 x Balb/c)F1 lymphoid cells leads to transient chimerism and runting, and to splenomegaly, deficient T-cell function and a gradual replacement of lymphoid organs with abnormal reticular cells. Activated MuLV can be isolated from such mice. It is proposed that either graft-versus-host or host-versus-graft allogeneic reactivity activates endogenous MuLV virus, which then causes functional and morphological abnormalities in the lymphoid organs.